Insulin resistance syndrome as a feature of cardiological syndrome X in non-obese men. Issue 1 (January 1994) - Swan, J. W.; Walton, C.; Godsland, I. F.; Crook, D.; Oliver, M. F.; Stevenson, J. C.
Abstract : OBJECTIVE--To assess the features of the insulin resistance syndrome in patients presenting with cardiological syndrome X, who experience angina despite angiographically normal coronary arteries. PATIENTS AND METHODS--14 Non-obese male patients with syndrome X and 38 symptom free, apparently healthy, male volunteers were studied. Insulin sensitivity (inversely related to insulin resistance) was measured by minimal modelling analysis of glucose and insulin concentrations during an intravenous glucose tolerance test. Serum lipids, lipoproteins, and apolipoproteins were also measured. RESULTS--Insulin sensitivity was 31% lower in the men with syndrome X (p < 0.05) and fasting insulin concentration was 30% higher (p < 0.05). The patient group also had 64% higher mean triglycerides (p < 0.001) and 20% lower mean high density lipoprotein cholesterol concentration (p < 0.01). Systolic blood pressure was also 10% higher in the syndrome X group (p < 0.01). There were no differences in total cholesterol, low density lipoprotein cholesterol or lipoprotein (a). CONCLUSION--These findings show that non-obese male patients with anginal chest pain but normal coronary arteries (syndrome X) are insulin resistant, hyperinsulinaemic, and have higher concentrations of triglycerides and lower high density lipoprotein cholesterol than healthy men. The insulin resistance syndrome may predispose to a spectrum of arterial disease capable of causing myocardial ischaemia.